Transcriptoma do músculo longissimus dorsi de bovinos machos adultos da raça Nelore - Castan, Eduardo Paulino [UNESP] (2014)
The transcriptome is the set and the amount of transcripts in a cell at a specific developmental stage or physiological condition. Understanding the transcriptome is essential for interpreting the functional elements of the genome and to reveal molecular constituents of cells and tissues. Considering the great importance of the beef market, the need and difficulty of improving meat quality, this research aimed to provide an overview of the complete longissimus dorsi (LD) transcriptome of Nellore cattle and to identify genes with differential expression profiles associated with muscle growth using RNA-seq. Ten mRNA samples of Nellore breed steers with two different muscle growth profiles from a herd participating of a breeding program were used. LD muscle samples were collected for RNA extraction and processing, sequencing and subsequent transcriptome analysis. In total, approximately 453 million fragments were sequenced and 14,876 known genes, 45,938 potential new genes and 10,960 potential new transcripts isoforms were identified. The expression levels of 12,082 genes were calculated and 110 have signicant differential expression values between the groups (p ≤ 0.01). The ontology terms relevance analysis identified 52 relevant terms among the differentially expressed genes, which 12 were associated with muscle development. In this study, we obtained the transcriptome of Nellore cattle longissimus dorsi muscle through next-generation sequencing, providing a valuable source of information about the bovine genome